Efficacy and Safety of Rituximab in Connective Tissue Disease related Interstitial Lung Disease - Fitzgerald, Deirdre Brigid; Moloney, Fiachra; Twomey, Maria; O'Connell, Oisin J; Cronin, Owen; Harty, Len; Harney, Sinead; Henry, Michael T (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
AbstractBackground:Pulmonary complications of connective tissue disease are being identified more frequently with the advent of more sophisticated radiological investigations. Limited previous studies have suggested Rituximab (RTX), a chimeric monoclonal antibody with activity against CD-20, may benefit connective tissue disease patients with pulmonary complications. We performed a retrospective analysis of the efficacy and safety of RTX in patients attending a tertiary referral centre. Methods:Ten patients treated with RTX for pulmonary complications of CTD in our institution were identified. Baseline demographics, pre- and post-treatment investigations and adverse events were documented with an average follow up time-frame of 12.3 months (range: 3 – 27). Statistical analysis was performed using the Wilcoxan Signed-Rank test in SPSS. Results:There was a statistically significant improvement in pulmonary function, with a mean increase of 19% in DLCO (median DLCO (ml/min/mmHg) pre-treatment vs. post-treatment: 13.94 vs. 19.34, p=0.028) and a mean increase of 13% in FVC (median FVC (L) pre-treatment vs. post-treatment: 3.47 vs.3.6, p=0.28). For patients with pulmonary fibrosis (n=7), CT severity was improved on post-treatment scan, though this did not reach statistical significance. There was a reduction in the number of nodules seen on the follow-up scans of two patients without fibrosis. No patient had a severe adverse reaction to RTX. Conclusions:Treatment with RTX resulted in an objective, measurable improvement in pulmonary function and/or radiological severity for the majority of patients included in the series. This was statistically significant despite the small numbers included. These results indicate a positive response to RTX with few complications of treatment.